Metal-Mediated Base Pairing of Rigid and Flexible Benzaldoxime Metallacycles - Maity S; Hande M; Lönnberg T (WILEY-V C H VERLAG GMBH, 2022)
Oligonucleotides incorporating a central C-nucleoside with either a rigid or flexible benzaldoxime base moiety have been synthesized, and the hybridization properties of their metallacyclic derivatives have been studied by UV melting experiments. In all cases, the metallated duplexes were less stable than their unmetallated counterparts, and the metallacyclic nucleobases did not show a clear preference for any of the canonical nucleobases as a base-pairing partner. With palladated oligonucleotides, increased flexibility translated to less severe destabilization, whereas the opposite was true for the mercurated oligonucleotides; this reflects the greater difficulties in accommodating a rigid Pd-II-mediated base pair than a rigid Hg-II-mediated base pair within the base stack of a double helix.